A Panel Cointegration Analysis of the Relation between Private and Government Consumption - Åsa Eriksson (Lund University, School of Economics and Management, Department of Economics, 2005)
This paper analyses the relation between private and government consumption in 23 OECD countries between 1970 and 2001. In particular it addresses the issue of whether government consumption is a substitute for or a complement to private consumption. The empirical analysis is made with panel cointegration analysis, using the newly developed CUSUM cointegration test by westerlund05. The method is extended by using a bootstrap technique to control for cross-sectional dependence. The results show that government consumption is a complement to private consumption for most of the countries and a substitute for only a few of the countries.
Keywords: C33; E21; E62; 330; Private consumption; Government consumption; Panel cointegration